Micro plásticos como agentes de contaminación en los principales afluentes del río Cumbaza - Flores Ruiz, Edwin Junior (2024)
The study focused on identifying the presence of microplastics (MP) in the main tributaries of the Cumbaza River, Morales district, San Martín Region, Peru. Eight sampling points were defined, with 3 samples collected at each point during August 2023, the dry season, with temperatures between 18.3°C and 32.5°C and a monthly precipitation of 68 mm. Sampling sites included Juan Guerra, La Banda de Shilcayo, Tarapoto, Morales, and San Antonio. 2582 MPs were identified: 46.28% filaments (1195 MPs), 42.84% fragments (1106 MPs), and 10.88% microspheres (281 MPs). Cluster analysis showed that filaments and fragments share similar profiles, suggesting common sources, while microspheres come from different sources. Principal component analysis (PCA) indicated that filaments are more dispersed, while fragments and microspheres are often found together, depending on the sampling point. The abundance of MPs was highest in filaments, followed by fragments and microspheres. The MPs' sizes varied: filaments between 1.87 μm and 4934.18 μm, fragments between 1.38 μm and 2104.94 μm, and microspheres between 0.19 μm and 512.72 μm. The predominant color was blue, followed by red, with a consistent distribution at all sampling points. This study reveals a considerable presence of PMs in the tributaries of the Cumbaza River, highlighting the need to implement measures to mitigate microplastic pollution in the region. The diversity and abundance of MPs suggest multiple sources of pollution, mainly anthropogenic, that affect these freshwater bodies